INVESTIGATING CULTURAL CONTENTS OF READING PASSAGES IN THE TESTS DEVELOPED BY ENGLISH TEACHERS IN A SENIOR HIGH SCHOOL - Faris, Ihsan Nur Iman (Universitas Pendidikan Indonesia, 2015)
AbstractCultural contents contained in reading passages need to be treated carefully due to their influence to shapethe readersâ€™ points of view. Since a test can include reading passages, careful selection of reading passages should also be conducted in a test development. This research is aimed at investigating what cultures are contained in the reading passages of the tests developed by the English teachers in a senior high school and the reasons why the reading passages were included. The methods employed in this research were textual analysis and case study. The data for textual analysis were collected from 24 reading passages from the tests developed by the English teachers of a senior high school in Cianjur, West Java, Indonesia. The information related to the problems of inclusion of cultural contents in the tests was collected from an interview. Among 24 reading passages in the tests, 10 reading passages were culture-neutral, while 14 reading passages contained cultural items.The findings show that in 14 reading passages, the culture contained are the target culture (40%) in the forms of naming, place, and season, the international culture (40%) in the forms of naming, place, and season,and the source culture (20%) in the forms of naming and place. Theunbalance proportion of the source culture can influence the readersâ€™ mindset and the result of the test due to familiarity issue of the materials. Regarding why this proportion is found in the tests, the teachers were not aware of the cultural content issue. Therefore, the proportion was not intentionally made. The unawareness of teacher can lead to the inclusion of inappropriate cultural contents in the tests. Hence, based on the findings, it is recommended that teachers be more aware of cultural contents in reading passages and develop a test with a more balance proportion of cultural contents in reading passages.Keywords: Cultural contents, the source culture, the target culture, the international culture, reading passages.Â AbstrakIsi budaya yang terkandung dalam wacana harus diperlakukan dengan hati-hati karena bisa mempengaruhi sudut pandang pembaca. Dikarenakan tes mencakup wacana, pemilihan wacana secara hati-hati juga harus dilakukan dalam pengembangan tes. Penelitian ini bertujuan untuk menyelidiki budaya apa yang terkandung dalam wacana-wacana di dalam tes yang dikembangkan oleh guru bahasa Inggris di SMA dan alasan mengapa wacana tersebut dimasukkan. Metode yang digunakan dalam penelitian ini adalah analisis tekstual dan studi kasus. Data untuk analisis tekstual dikumpulkan dari 24 wacana dari tes yang dikembangkan oleh guru bahasa Inggris dari SMA di Cianjur, Jawa Barat, Indonesia. Informasi yang berhubungan dengan masalah masuknya isi budaya dalam tes dikumpulkan dari wawancara. Di antara 24 wacana tes, 10 wacana netral dari budaya, sementara 14 mengandung temuan budaya. Hasil menunjukkan bahwa dari 14 wacana, budaya yang terkandung adalah budaya target (40%) dalam bentuk penamaan, tempat, dan musim, budaya internasional (40%) dalam bentuk penamaan, tempat, dan musim, dan budaya sumber (20%) dalam bentuk penamaan dan tempat. Proporsi budaya yang tidak imbang dapat mempengaruhi pola pikir pembaca dan hasil tes karena berkaitan dengan tingkat pengetahuan terhadap materi. Mengenai mengapa proporsi ini ditemukan dalam tes, guru tidak menyadari masalah konten budaya. Oleh karena itu, proporsi tidak sengaja dibuat. Ketidaksadaran guru dapat menyebabkan masuknya isi budaya yang tidak pantas ke dalam tes. Oleh karena itu, berdasarkan temuan, disarankan bahwa guru menjadi lebih sadar akan isi budaya dalam wacana dan mengembangkan tes dengan menjaga keseimbangan proporsi isi budaya dalam wacana.Kata kunci: Isi budaya, budaya sumber, budaya target, budaya internasional, wacana.